Atom probe tomography of interfaces in ceramic films and oxide scales. (January 2016) - Stiller, K.; Thuvander, M.; Povstugar, I.; Choi, P.P.; Andrén, H.-O.
Abstract: Abstract : Atomic-scale characterization of interfaces in ceramic materials is needed in order to fully understand their electronic, ionic, mechanical, magnetic, and optical properties. The latest development of laser-assisted atom probe tomography (APT), as well as new specimen preparation methods, have opened the realm of ceramics for structural and chemical characterization with high sensitivity and nearly atomic spatial resolution. This article reviews recent APT investigations of interfaces in thin nitride films and thermally grown oxides: TiAlN layers and oxide scales on alumina- and chromia-formers and Zr alloys. The selected examples highlight the role of interfaces in the decomposition of films and in transport processes.